Influence of biomass type on its characteristics of convective heating and dehydration. (November 2021) - Kuznetsov, G.V.; Nigay, N.A.; Syrodoy, S.V.; Gutareva, N.Yu.
Abstract: The paper presents the results of experimental studies of the drying processes of forest biomass, which is promising for energy purposes, - branches of various types of wood: birch, linden, poplar. The experiments were carried out on an installation that provides a low level of error (no more than 8.5%) for measuring the main significant parameters and characteristics of the dehumidification process. According to the results of the experiments, the integral characteristics of the greatest interest (times of complete dehydration) of the drying process have been established. Based on the results of the experiments, a non-monotonic change in the rates of moisture removal was established (the values of W eva increase and decrease with time) at a low-temperature heating mode (at Tg < 373 K). At the same time, under conditions of relatively high ambient temperatures (Tg ≥ 373 K), such a change in W eva does not occur. The authors formulated a hypothesis explaining the physical mechanism of such a dependence of the mass rate of moisture removal ( W eva ) on time. An energy analysis of the drying efficiency of three types of biomass has been carried out. It has been shown that branches of birch, poplar and linden are most efficiently dried in conditions of relatively low temperatures (333 ≤ Tg ≤ 353 K). At the same time, it was found that for birch and poplar branches, an increase in the ambient temperature leads to a decrease in the efficiency of the drying process of woody biomass. Highlights: Two temperature regimes have been highlighted for drying wood branches. Under low-temperature heating conditions, the drying rate changes non-monotonously. At relatively high ambient temperatures, the drying rate changes monotonously. Tree branches are dried more efficiently at moderate ambient temperatures.